Clinical Examples of the Use of Mercureid Drug in Patients with Ischemic Neuropathy of the Optic Nerve That Appeared After Long COVID-19 - Величко, Людмила Миколаївна; Богданова, Олександра Вікторівна; Храменко, Наталія Іванівна; Коновалова, Наталія Валеріївна (My University, 2021)
Most people with coronavirus disease 2019 (COVID-19) recover completely within a few weeks. But some people continue to experience symptoms after the initial recovery. This condition is called post-COVID-19 syndrome or long COVID-19. They are threatened by the development of various diseases. We tried to answer some of these questions in our research. The study was conducted in 49 patients with ophthalmic pathologies who had previously undergone COVID-19. On the one hand, ocular pathologies are important because they allow in a non-traumatic way to obtain lifetime visualization of the state of blood vessels and capillaries as well as to assess the effect of the virus on the central nervous system.
Keywords: Pupil; Optic Neuritis; Optical Coherence Tomography; Cornea